2013
DOI: 10.1080/09658211.2012.727006
|View full text |Cite
|
Sign up to set email alerts
|

Ironic effects of compulsive perseveration

Abstract: Individuals with obsessive-compulsive disorder (OCD) exhibit perseverative behaviours, like checking, to reduce uncertainty, but perseveration paradoxically enhances uncertainty. It is unclear what mechanism might be responsible. We hypothesised that perseverative OC-like behaviour produces "semantic satiation" and interferes with the accessibility of meaning. Healthy participants repeated 20 types of OC-like checking behaviour nonperseveratively (2 times) or perseveratively (20 times). Afterwards, they decide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 26 publications
0
20
2
Order By: Relevance
“…These findings may be prima facie viewed as contradictory to the meta-memory deficit theory, which claims that diminished confidence in memory abilities contribute to compulsive checking. Indeed, prior findings have consistently described the ‘ironic effects’ of repeated checking behaviours (Giele et al 2013) that reduce confidence in memory and increase uncertainty (Van den Hout & Kindt, 2003 a , b ; Coles et al 2006; Radomsky et al 2006; Ashbaugh & Radomsky, 2007; Boschen & Vuksanovic, 2007; Cuttler & Graf, 2009 a ; Dek et al 2010; Giele et al 2013; Toffolo et al 2013), whereas we described a diminished ability to detect a visuospatial difference in the present study. Furthermore, like healthy subjects, the OCD patients were asked to answer only if they were certain of their answer, i.e.…”
Section: Discussionmentioning
confidence: 94%
“…These findings may be prima facie viewed as contradictory to the meta-memory deficit theory, which claims that diminished confidence in memory abilities contribute to compulsive checking. Indeed, prior findings have consistently described the ‘ironic effects’ of repeated checking behaviours (Giele et al 2013) that reduce confidence in memory and increase uncertainty (Van den Hout & Kindt, 2003 a , b ; Coles et al 2006; Radomsky et al 2006; Ashbaugh & Radomsky, 2007; Boschen & Vuksanovic, 2007; Cuttler & Graf, 2009 a ; Dek et al 2010; Giele et al 2013; Toffolo et al 2013), whereas we described a diminished ability to detect a visuospatial difference in the present study. Furthermore, like healthy subjects, the OCD patients were asked to answer only if they were certain of their answer, i.e.…”
Section: Discussionmentioning
confidence: 94%
“…If one repeats a word 10 times, the meaning of the word is retained on an intellectual level, but the word starts to feel disconnected from its meaning on a phenomenological level (Brewin, Ma, & Colson, 2013;Brewin & Mersaditabari, 2013). Similarly, a different form of perseveration (e.g., prolonged fixation on an object, checking or repeating sentences) can bring about similar experiences of dissociation and specifically DEP-DER (Giele et al, 2013(Giele et al, , 2014Sanbonmatsu et al, 2007;van den Hout et al, 2008van den Hout et al, , 2009. Notably, in these experiments the repetition was willed and neutral, whereas in rumination, the repetitive thoughts are negative and intrusive.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that checking compulsions in OCD patients stem from deficits in other functional domains, such as lack of memory confidence leading to patients mistrusting memories that they know are accurate (MacDonald et al, 1997; Tolin et al, 2001; van den Hout & Kindt, 2003). Interestingly, several studies have suggested that repeated checking directly decreases memory confidence, even in healthy controls, which may give hints about the origin of compulsive checking (Giele et al, 2013; Harkin & Kessler, 2009; Harkin & Kessler, 2011; Harkin, Rutherford, & Kessler, 2011; van den Hout & Kindt, 2004). Other factors that may contribute to the evolution of checking compulsions include feelings of incompletion, doubt, and uncertainty (Jacoby, Fabricant, Leonard, Riemann, & Abramowitz, 2013; Tolin, Abramowitz, Brigidi, & Foa, 2003); increased salience of imagined feared outcomes (Psychometri, 2005; Salkovskis, 1985); and/or overestimation of the likelihood of occurrence of feared events (Cisler & Koster, 2010; Jones & Menzies, 1997; Jones & Menzies, 1998; Moritz & Jelinek, 2009).…”
Section: Discussionmentioning
confidence: 99%